KUALITAS ASAP CAIR BATANG GELAM (Melaleuca sp.) - Alpian Alpian; Tiberius Agus Prayitno; Johanes Pramana; Gentur Sutapa; Budiadi Budiadi (Jurnal Penelitian Hasil Hutan, 2014)
Gelam ( Melaleuca sp. ) Is a tidal marsh species that grow in the swamp forests of South Kalimantan and Central Kalimantan. Gelam is one of the species of timber-producing potential as liquid smoke with the technology available and easy to implement. This paper study the possible uses of softwood for liquid smoke. Liquid smoke derived from wood pyrolysis process at a temperature of 500 ° C for 3 hours. Liquid smoke is a reddish yellow, transparent and no floating material. Liquid smoke density is 1.008 to 1.058 with 3.105 to 3.195 pH and acidity varied from 5.167 to 12.903%. Carbonyl and phenol levels respectively is 11.250 to 28.307% and 2.429 to 9.231%. In general, softwood produce liquid smoke and meets quality requirements of Japanese standards.